Mixed Effects of Deep Brain Stimulation on Depressive Symptomatology in Parkinson’s Disease: A Review of Randomized Clinical Trials - Gökbayrak, N. Simay; Piryatinsky, Irene; Gavett, Rebecca A.; Ahmed, Omar J. (Frontiers in Neurology, 2014)
Although ~50% of patients with Parkinson’s disease (PD) experience depression, treatment for this important and debilitating comorbitidy is relatively understudied. Deep brain stimulation (DBS) has been increasingly utilized for the management of tremors in progressive PD. Several preliminary studies have shown the potential benefit of DBS for non-motor PD symptoms such as depression. Here, we critically evaluate seven recent randomized controlled trials (RCT) of the effectiveness of DBS in reducing depressive symptomatology among individuals with PD. Findings are mixed for the effectiveness of DBS as a treatment for depression in PD. Our review suggests that is due, in large part, to the anatomical and methodological variation across the DBS studies. We provide a comprehensive discussion of these variations and highlight the need to conduct larger, more controlled studies aimed specifically at evaluating the treatment of depression in PD patients.